Faktor Yang Berhubungan Dengan Kejadian Pre-Eklampsia Pada Ibu Hamil Di RSUD Rupit - Rahmadiani, Yeni; Azissah, Danur; Habibi, Julius (Gayaku Publisher, 2023)
Preeclampsia is a specific syndrome of pregnancy with decreased organ perfusion that results in vascular vasospasm and endothelial activation, which is one of the leading causes of death in mothers. The purpose of this study was to determine the factors associated with the incidence of preeclampsia at Rupit Hospital in 2022. The method used was a descriptive research design with a cross-sectional approach. The number of respondents was 86. This study used the Chi-Square test.The results of univariate analysis obtained in the form of almost all of the respondents did not experience preeclampsia as many as 66 respondents (76.6%), almost half of the respondents had secondary education as many as 38 respondents (44.2%), most of the respondents had an average income of UMRsebanyak as many as 60 respondents (69.8%), and most of the respondents had good knowledge as many as 53 respondents (61.6%). While the bivariate results showed that there was a relationship between education and preeclampsia (p-value: 0.009), average income with preeclampsia (p-value: 0.013), and knowledge with preeclampsia (p-value: 0.004), Patients are expected to increase their knowledge and education so that they have the possibility of increasing their income, which can help prevent preeclampsia.